Use of horizontal subsurface flow constructed wetlands to treat reverse osmosis concentrate of rolling wastewater. Issue 3 (4th March 2017) - Xu, Jingcheng; Zhao, Gang; Huang, Xiangfeng; Guo, Haobo; Liu, Wei
ABSTRACT: According to the characteristics of the reverse osmosis concentrate (ROC) generated from iron and steel company, we used three sets of parallel horizontal subsurface flow (HSF) constructed wetlands (CWs) with different plants and substrate layouts to treat the high-salinity wastewater. The plant growth and removal efficiencies under saline condition were evaluated. The evaluation was based entirely on routinely collected water quality data and the physical and chemical characteristics of the plants ( Phragmites australis, Typha latifolia, Iris wilsonii, and Scirpus planiculmis ). The principal parameters of concern in the effluent were chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP). The results showed that the CWs were able to remove COD, TN, and TP from ROC. S. planiculmis was not suitable for the treatment of high-saline wastewater. The sequence of metals accumulated in CW plants was K>Ca>Na>Mg>Zn>Cu. More than 70% of metals were accumulated in the aboveground of P. australis . The CW filled with gravel and manganese ore and planted with P. australis and T. latifolia had the best performance of pollutant removal, with average removal of 49.96%, 39.45%, and 72.01% for COD, TN, and TP, respectively. The effluent water quality met the regulation in China. These results suggested that HSF CW planted with P. australis and T. latifolia can be applied for ROC pollutants removal.